2024
DOI: 10.1111/dar.13854
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐elimination of chronic hepatitis C virus in mental health settings: A prospective multicentre pragmatic trial

Cameron Gofton,
Kindness Bondezi,
Beth Kotze
et al.

Abstract: IntroductionHepatitis C virus (HCV) prevalence is high in the mental health population. We sought to evaluate testing and treatment uptake for HCV following the implementation of a universal nurse led study in inpatient and outpatient mental health populations.MethodsFrom January 2018 to December 2020, we screened mental health inpatients (n = 322) and community mental health patients (n = 615) for HCV with either specialist hepatology nurses or mental health nurses (mental health nurse).Results75.5% (464/615)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Mental health services are increasingly being identified as an opportunity to provide hepatitis C care [ 6 , 7 , 41 ]. A recent study in Australia showed a DAA treatment uptake of 46% in mental health inpatients with hepatitis C [ 42 ]. Antenatal inpatients, in whom there is a relatively high rate of hepatitis C testing due to inclusion in standard antenatal serology, would benefit from a collaborative care model that coordinates hepatitis C treatment and care post pregnancy, inclusive of infant testing, similar to those in place for hepatitis B [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mental health services are increasingly being identified as an opportunity to provide hepatitis C care [ 6 , 7 , 41 ]. A recent study in Australia showed a DAA treatment uptake of 46% in mental health inpatients with hepatitis C [ 42 ]. Antenatal inpatients, in whom there is a relatively high rate of hepatitis C testing due to inclusion in standard antenatal serology, would benefit from a collaborative care model that coordinates hepatitis C treatment and care post pregnancy, inclusive of infant testing, similar to those in place for hepatitis B [ 43 ].…”
Section: Discussionmentioning
confidence: 99%